KAJIAN PEMANFAATAN DEM SRTM & GOOGLE EARTH UNTUK PARAMETER PENILAIAN POTENSI KERUGIAN EKONOMI AKIBAT BANJIR ROB - Arief L Nugraha; Hani’ah Hani’ah (TEKNIK, 2013)
Tidal flood is a significant threat for the economic growth rate in the city of Semarang. The threat mitigation requires planning, thereby reducing the impact of the losses. The availability of global data with free access can provide solutions in disaster management, the data are SRTM DEM and Google Earth. With both of these data can be mapped potential economic losses caused by tidal flooding. With the techniques of remote sensing and GIS to handle the SRTM DEM data and Google Earth, the techniques can be generated maps and models of tidal inundation area maps woke up in the city of Semarang. Analysis of potential economic losses can be calculated by doing an overlay of the two maps generated. The results achieved from this study is SRTM DEM and Google Earth can able to produce thematic maps of situational tidal flood disaster so that it can be used as a parameter value calculation of the potential economic losses. This study also obtain the result that the area of ​​land affected by the tidal flood an area of ​​8339.31 hectares and the number of buildings reaching 78 299 pieces, which the district that has the highest impact on the tidal flood that North Semarang.